Inferring humor. A model of analysis for Spanish. - Ruiz Gurillo, Leonor (Círculo de Lingüística Aplicada a la Comunicación, 2014)
This article examines humor in Spanish, according to a pragmatic model. Thus, a neo-gricean explanation (Rodríguez Rosique, 2009; 2013) shows that the transgression of Quality may alter the standard working of Conversational Principles through e.g. prosodic markers. Thus, the explicit transgression of Quality (through a humorous mode) may affect to the Quantity-, Manner- or/and Informativity-Principles. Indicators like quantifiers (a buenas horas), marked expressions, such as phraseological units (¡que le parta un rayo [a alguien]!) or code-switching –technical/informal register (¡me la suda!/melasuda/melasudina), polysemy (coronas) or paronomy (Estatut/vermut) are implicated to obtain humorous effects.